Pengembangan Modul Tematik Berbasis Kearifan Lokal Sebagai Sumber Belajar IPS - Ahimsa Tunggul Ernandi; Rusmawan Rusmawan; Puji Purnomo (PAKIS (Publikasi Berkala Pendidikan Ilmu Sosial), 2022)
This research is motivated by the lack of teaching materials based on local wisdom in elementary schools. The purpose of this study was to develop teaching materials in the form of thematic modules based on local wisdom about the uniqueness of the Gunungkidul Regency area that was suitable for fourth-grade elementary school students. This research used Research and Development (R&D). This research procedure used the ADDIE model, namely analyze, design, develop, implement, and evaluate. The subjects of this study were experts, teachers, and four-grade elementary school students. This research used interview guidelines, expert validation questionnaires, and response questionnaires obtained from teachers and students. Data collection techniques used were observation, interviews, and questionnaires. This research used qualitative and quantitative techniques to analyze the data. Expert assessment results showed that the modul is considered appropriate to be tested in which this decision is previously proven by the validation from the instructional media expert and thematic learning expert. The validation score from the instructional media expert is 3,00 (good category). The validation score for thematic learning expert is 3,36 (very good category). The average score of teachers’ questionnaire responses is 3,66 (very good category). The average score of the limited trial is 3,48 (very good category). The implication of this research is the need to disseminate the idea of using local wisdom for social studies learning resources.Keywords: teching materials, thematic modul, local wisdom